Improving the Quality of Children's Ramadan Activities Through Community Service - Ade Muhammad Ritonga; Hana Khoirany Sinaga; Fina Rizkiyah Hasibuan; Uswatun Hasanah; Dina Febrina; Isna Aprila; Lailatul Fiska Sya'bani (As-sunnah: Jurnal Pengabdian Masyarakat, 2022)
During Ramadan, the enthusiasm of the Muslim community to worship increases rapidly, but their enthusiasm tends not to get a container or not to be supported. This is due to a shortage of teachers, mentors, facilities, and others. Therefore, STAI As-sunnah students carry out community service activities to help make activities successful during Ramadan, especially for children. The research method used is the Participatory Action Research (PAR) research method. In PAR activities, researchers do not separate themselves from the situation of the community being studied but instead, merge into it and work with residents in conducting PAR. Then, PAR is oriented towards changing the situation, increasing the knowledge and ability of citizens to understand and change their situation for the better. In this study, activities will be centered on children. The results of community service include the field of education, a field of religion, and the field of creation or creativity. In education, it has successfully trained children in public speaking, introduced Arabic to children, and provided material on Sirah nabawiyah. Then, one day-one juz has been successfully carried out in the religious field, regular Ramadan studies, sentence thayyibah, and other positive activities. Finally, in the field of creation, origami creations and jelly cooking creations are carried out. All programs have been implemented well, and this has received support from all members of the village community, who are full of enthusiasm and excellent and high spirits, so the programs implemented are beneficial and can be realized. Hopefully, the activities will continue to run continuously after the community service activities are completed.